2016
DOI: 10.1021/acs.biochem.5b01315
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations Reveal the Conformational Flexibility of Lipid II and Its Loose Association with the Defensin Plectasin in the Staphylococcus aureus Membrane

Abstract: Lipid II is critical for peptidoglycan synthesis, which is the main component of the bacterial cell wall. Lipid II is a relatively conserved and important part of the cell wall biosynthesis pathway and is targeted by antibiotics such as the lantibiotics, which achieve their function by disrupting the biosynthesis of the cell wall. Given the urgent need for development of novel antibiotics to counter the growing threat of bacterial infection resistance, it is imperative that a thorough molecular-level character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 47 publications
7
34
0
Order By: Relevance
“…It has recently been shown that modulation of either MreBCD or PBP1 levels is sufficient to alter the shape of B. subtilis cells 41 , underscoring the importance of both systems. In the absence of flotillins, the activity of the MreBCD component is strongly reduced – as evidenced by the reduction of MreB speed – and the overall rigidity of the membrane is increased which results in a less favourable environment for the peptidoglycan precursor LipidII, which prefers more liquid, disordered membrane phases 11,12,42 . To compensate, membrane fluidity and peptidoglycan synthesis activity is increased at division sites in flotillin mutants, which is sufficient to keep the overall cell shape intact, although cells are elongated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has recently been shown that modulation of either MreBCD or PBP1 levels is sufficient to alter the shape of B. subtilis cells 41 , underscoring the importance of both systems. In the absence of flotillins, the activity of the MreBCD component is strongly reduced – as evidenced by the reduction of MreB speed – and the overall rigidity of the membrane is increased which results in a less favourable environment for the peptidoglycan precursor LipidII, which prefers more liquid, disordered membrane phases 11,12,42 . To compensate, membrane fluidity and peptidoglycan synthesis activity is increased at division sites in flotillin mutants, which is sufficient to keep the overall cell shape intact, although cells are elongated.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of flotillins, the activity of the MreBCD component is strongly reduced – as evidenced by the reduction of MreB speed – and the overall rigidity of the membrane is increased. This results in a less favourable environment for the peptidoglycan precursor LipidII, which prefers more liquid, disordered membrane phases 14,15,47 . Our data indicate that the reduction in elongasome activity, which does not impact the growth rate itself, is compensated by increased peptidoglycan synthesis activity around division sites in flotillin mutants, which is sufficient to keep the overall cell shape intact, although cells are elongated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in a related study we were able to solve the X-ray structure of the isofunctional homologue of MurM from S. aureus (FemX), which we have used here as a template for homology modelling of MurM. Using this MurM homology model we have successfully identified the Lipid II binding site, and used molecular dynamics (MD) simulations to investigate interactions between MurM and both membrane phospholipids and its Lipid II substrate (Witzke et al, 2016). We subsequently, studied the effects of these membrane embedded phospholipids, on the enzymatic activity of MurM in vitro, corroborating our in silico analysis.…”
mentioning
confidence: 99%